An Umbelliferone-induced Caspase-Mediated Apoptosis in MDA-MB-231 Breast Cancer Cells - Albratty, Mohammed; Makeen, Hafiz A (Indian Journal of Pharmaceutical Education and Research, 2024)
Background A highly malignant tumor, Breast Cancer (BC) has a poor prognosis for patients with the highest mortality rates in women. BC is currently treatable with a limited number of therapeutic strategies. Aim Natural compounds with anti-proliferative capabilities are gaining popularity as a way to mitigate the toxicity of radiation and synthetic anti-tumor drugs. Umbelliferone has been reported to possess diverse pharmacological activities, like anti-cancer, anti-inflammation and anti-oxidation properties. Materials and Methods In the current investigation, the potential of umbelliferone as an anti-cancer agent for breast cancer was evaluated in MDA-MB-231 cell lines. The influence of umbelliferone on cell viability AO/EtBr, apoptotic induction, MMP levels, ROS generation, cell adhesion assays, apoptotic marker levels and anti-inflammatory has been examined. Results The impact of umbelliferone on the cell viability revealed that its cytotoxic potential increased in a dose-dependent pattern and IC50 concentrations were chosen for further experiments. The results showed that apoptosis was induced by umbelliferone in MDA-MB-231 cells by staining with AO/EtBr, triggering ROS pathway and DNA damage level of MMP. The caspase and inflammatory marker levels were also increased upon umbelliferone treatment. Conclusion Umbelliferone cytotoxic potential in cells is mediated by inducing apoptosis, which is supported by significant levels of ROS and MMP level as well as the findings of the staining. All these results suggest that umbelliferone can be used as a potent anti-cancer drug for breast cancer cells.
Keywords: Breast cancer; Umbelliferone; MDA-MB-231 cells; Apoptosis; Reactive oxygen species